Comparison of Learning Outcomes Between Online-Based and Paper-Based Assessments on Digital Document Elements in Yogyakarta State Vocational High School - Heni Setiyaningsih; Yuliansah, Yuliansah (Journal of Office Administration : Education and Practice, 2025)
This study aims to compare the exam results of paper-based and online-based assessments among vocational high school students majoring in Office Management and Business Services. The research employed a quasi-experimental method with a post-test only control group design. Using purposive sampling, the study involved 32 tenth-grade students from the Office Management program as the experimental group and tenth-grade students from the Logistics Management program as the control group at Yogyakarta State Vocational High School. The results showed an average score of 65.16 for the experimental group and 68.97 for the control group. This indicates that students who took the paper-based exam achieved higher average scores than those who took the online-based exam. These findings provide empirical evidence that there is a significant difference between paper-based and online-based exam results among vocational students. The study also demonstrates that the choice of exam method has an impact on students’ learning outcomes.